Implementasi Kebijakan Pembentukan dan Pengelolaan Badan Usaha Milik Desa di Indonesia: Policy Implementation on Establishment and Management of Village-Owned Enterprises in Indonesia - Andy Alfatih; Diana Dewi Sartika; Dyah Hapsari Eko Nueraheni (Society, 2021)
One of the efforts to obtain and increase village revenue was by running a business through a village-owned enterprise (VOEs). A policy was needed for utilizing village resources in establishing a village-owned enterprise. The Musi Rawas Regency Government had made a policy, namely Musi Rawas Regency Regional Regulation Number 10 of 2013, concerning Guidelines for the Establishment and Management of Village-Owned Enterprises (VOEs). Villages of Musi Rawas Regency had implemented this regulation. This research aimed to evaluate the implementation of this regional regulation. This research method is descriptive quantitative comprises a sample survey and descriptive analysis indicators resulting from the sample survey. The population of this research was 174 Village-Owned Enterprises (VOEs/BUMDes) in Musi Rawas Regency. At the same time, the sample was 64 VOEs which was taken by referring to the Slovin formula. There were primary data and secondary ones. Primary data came mainly from the questionnaire and field observation. Meanwhile, secondary data were sourced from documents, such as archives and reports. Data were analyzed by descriptive technique. The descriptive technique was done by displaying data, assessing them, delivering argument, quoting theory for justification and confirmation, and concluding. Implementing the Regional Regulation concerning Guidelines for the Establishment and Management of Village-Owned Enterprises (VOEs) was successful. This could be seen from several indicators, refers to Ripley & Franklin (1986), namely: 1) There existed compliance of policy implementers towards the content of the regional regulation. The degree of compliance was high and was in a good category. 2) The establishment and management of VOEs (the smoothness of routine functions) were also high and classified as good, and 3) The performance of the management of VOEs was also good. The impact of policy implementation (regional regulation of Musi Rawas Regency) was positive (good).